EVALUASI TAJAM PENGLIHATAN DAN INDEKS PROPTOSIS PASIEN MENINGIOMA SPHENOORBITA PASCAOPERASI KRANIEKTOMI - Renindra Ananda Aman,* Ryan Rhiveldi Keswani,* Syaiful Ichwan,* Samsul Ashari, Setyo Widi Nugroho* (NEURONA, 2020)
INTRODUCTION SPHENOORBITAL MENINGIOMA SOM IS AN EXOPHYTIC TUMOR MASS THAT INFILTRATES THE BONE AT THE SPHENOID WING LATERAL ORBITAL WALLS ORBITAL ROOFS AND EXTENDS TO SUPERIOR ORBITAL FISSURES THE CLASSIC TRIAD OF CLINICAL FEATURES ARE PROPTOSIS DECREASED VISUAL ACUITY AND OPHTHALMOPLEGIA THE OUTCOMES OF OUR POSTOPERATIVE PATIENTS HAVE NOT BEEN EVALUATED BEFORE